Perancangan dan Aplikasi Distilasi Minyak Serai Wangi Menggunakan Photovoltaic dengan System Tenaga Hybrid - Mutia, Ulfa; Rihayat, Teuku; Syafruddin, Syafruddin (Jurnal Teknologi, 2024)
UUtilization of sunlight is currently very effective as a renewable energy. Photovoltaic systems are modules that are used to absorb heat exposed to sunlight which is converted into electrical energy. The amount of potential sunlight that can be absorbed depends on the size of the cell and the absorption capacity of solar cells against sunlight. This study uses 4 solar panels to produce heat which is used for the essential oil production process. The total power that can be generated within 6 hours is 8664 kJ. Based on the test results of the distillation tool design using solar cells, energy absorption efficiency is not 100% absorbed due to lost energy and the number of solar panels used has not reached the power requirement, but to overcome this, during the study a hybrid power system was also used, where power is also supplied from the mains National Electric Company (PLN). Test results on citronella oil (Chimbopogan Nardus L) are close to SNI standards. The optimum drying time to produce the highest % yield is 1 day of drying time with 6 hours of distillation time. The results of citronella produced met Indonesian quality standards, where the density test value was 0.8869, and Gas Chromatography-Mass Spectrometry (GC-MS), namely citronella content of 15.75% at a retention time of 15.875 minutes. Geraniol content in essential oil was obtained at 28.70% retention time of 18.050 minutes which are within the range of the Indonesian National Standard (SNI) 2385-2006.